Analisis faktor penyebab kesulitan peserta didik dalam pembelajaran menulis aksara jawa kelas v sd - Reizka, Adhna Aini Nur; Winarni, Retno; Daryanto, Joko (Didaktika Dwija Indria, 2024)
Adhna ‘Aini Nur Reizka. ANALYSIS OF FACTORS CAUSING DIFFICULTIES IN JAVANESE LEARNING ESPECIALLY ON WRITING JAVANESE FONTS (AKSARA JAWA) AT CLASS V SDN KABANGAN NO. 55 SURAKARTA. Skripsi. Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta. January 2023.This study aims to (1) find out the factors that cause difficulties in learning to write Javanese script for class V at SDN Kabangan No. 55 Surakarta (2) explains the reasons for the emergence of difficulties experienced in learning to write Javanese script for class V at SDN Kabangan No. 55 Surakarta and provide alternative solutions. This research is a qualitative descriptive study, using analytical techniques according to the Miles and Huberman model and data validity testing techniques using technique and source triangulation. The discussion of this study contains a description of the difficulties of learning to write Javanese script experienced by fifth grade students at SDN Kabangan no. 55 Surakarta is seen based on indicators of writing difficulty, namely writing accuracy/consistency, clarity of writing form, and writing neatness. After presenting a description of the difficulties in learning to write Javanese script, the researcher will present the results of an analysis of the factors that cause difficulties in learning to write Javanese script, based on the results of the data obtained and processed in the odd semester lessons, October-November 2022, and the researcher provides various alternatives in overcoming the factors that cause the emergence of The difficulty of learning to write the script is divided into 2, namely, factors from within the students (internal), and factors that come from outside the students (external) based on previous scientific studies, ideas from the class teacher as resource persons, and the researcher's personal opinion.